Management of chickpea pod borer, helicoverpa armigera (Hubner) using neem seed extract and lambda-cyhalothrin in high barind tract - Hossain, MS; Islam, MS; Salam, MA; Hossain, MA; Salma, MU (Journal of Bio-Science, 2011)
Context: Lamda cyhalothrin and neem seed extract can protect chickpea by controlling pod borer Helicoverpa armigera (Hubner). Objective: To find out the effect of neem seed extract and lambda-cyhalothrin application schedule for the effective and economic management of pod borer attacking chickpea. Materials and Methods: The experiments were conducted in High Barind Tract of northern Bangladesh with the application of neem seed extract @ 50 g-l (two and three spraying) and lambda-cyhalothrin. (Karate 2.5 EC) @ 2 ml-l (two and three spraying) and untreated control. The seeds of BARI-Chola 5 chickpea were sown in rows with the spacing of 40 cm. At maturity, all the pods were collected from 10 randomly selected plants from middle rows of each plot. The damaged (bored) and total numbers of pod were counted. The grain yield loss (kg-ha) and percent pod damage were determined. The seed yield of each treatment was converted to kg-ha. Results: The lowest pod damage (2.55%) as well as grain yield loss (34.90 kg-ha) were observed in the treatment where lamda cyhalothrin applied three times at 7 days interval from flowering stage. Chickpea seed yield was maximum (1338 kg-ha) with lamda cyhalothrin sprayed thrice which was identical to sprayed twice (1280 kg-ha). Neem seed extract showed a marginal performance to control chickpea pod borer. The highest marginal benefit cost ratio (3.19) was recorded from lamda cyhalothrin sprayed twice. Conclusion: Lamda cyhalothrin double sprayed with 7 days interval from pod formation stage is the best package in managing pod borer in chickpea considering efficacy and profitability. Keywords: Chickpea; pod borer; pod damage; pesticides; yield. DOI: http://dx.doi.org/10.3329/jbs.v18i0.8774 JBS 2010; 18(0): 44-48